Analisis Kepuasan Menggunakan Aplikasi DANA dengan Menerapkan Metode TAM - Prayoga, Nopri; Nesya, Sindi Apri (CV. Graha Mitra Edukasi, 2023)
Currently, technology has been present in helping to facilitate human work so that human work is easier and more effective. The role of technology in various aspects of activities can be understood. Technology has penetrated into the financial sector by using intelligent systems. One of the smart system technologies is the DANA application. The DANA application is an abbreviation of Dompet Digital Indonesia which is based on a mobile application. The various conveniences offered, from buying food, topping up credit, and paying bills have made many people use them, especially the younger generation. Sometimes, we want to measure the level of user satisfaction of the DANA application so that we can find out how easy and friendly the DANA application is. For this reason, a research is needed to determine customer satisfaction or the user of the DANA application. The method that can be used to determine the level of customer or user satisfaction is to apply the technology acceptance model (TAM) method. This model is a model of acceptance of information technology systems that will be used by users. This research is expected to provide the optimal solution in analyzing customer satisfaction or DANA application users